Teriflunomide-exposed pregnancies in a French cohort of patients with multiple sclerosis. Issue 4 (August 2020) - Barataud-Reilhac, Astrid; Kerbrat, Sandrine; Roux, Jonathan; Guilleux, Alice; Polard, Elisabeth; Leray, Emmanuelle
Abstract : Objective: To describe pregnancies exposed to teriflunomide (TERIF) in women with multiple sclerosis (MS) in France over the period 2014–2016. Methods: All 15- to 49-year-old women with MS in the national health insurance database were included. Pregnancies that had started between August 2014 and March 2016 were identified from their outcomes. Three groups according to treatment exposure were compared: TERIF, interferons (IFNs) or glatiramer acetate, and no medication. Results: Among the 44, 008 women with MS followed 24.5 months on average, 2, 639 pregnancies were identified. There were 1, 538 pregnancies (58.3%) that were not exposed to any MS treatment in accordance with the guidelines. A total of 673 pregnancies (25.5%) were exposed to IFN and/or glatiramer acetate, and possible or probable exposure to contra-indicated treatments was observed in 428 pregnancies (16.2%), of whom 47 pregnancies were exposed to TERIF. The annual incidence rate of pregnancies exposed to TERIF was 1.4 per 100 patient-years; i.e., 3 times less than the 2 control groups (5.6 and 4.7, respectively). The median exposure duration to TERIF was 45 days after conception. The outcomes comprised 23 live births, 22 abortions (3 times more than the 2 other groups), and 2 miscarriages. All newborns were healthy at birth. Conclusions: Despite specific TERIF guidelines for pregnancy-related issues and the availability of alternative therapies, some pregnancies exposed to TERIF were identified. Most of the cases were because of the absence of the recommended accelerated elimination procedure and appeared to be mostly unplanned pregnancies that probably reflect a lack of effective contraception.